He Effect of Employee's Distribution and Authority on Employee Performance at PT. Huki Branch Medan - Teddy Pribadi (Formosa Journal of Multidisciplinary Research, 2022)
The Effect of Consumer Perception and Marketing Strategy on Increasing Sales of Kokita in Medan ", Thesis, 202 The purpose of this study was to investigate and analyze the Effect of Consumer Perception and Marketing Strategies on Increasing Sales of Kokita in Medan. The research method used is associative research, where variables are measured on a Likert scale. The method of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were all consumers of Kokita products in Medan city, which totaled 126 people. Sampling with saturated sampling method or better known as the census. In this study the total population is relatively small as many as 126 people. Data processing using SPSS software version 23, with descriptive analysis and hypothesis testing multiple regression analysis.The results showed that: (1) partially Consumer Perception variables influenced Increased Sales of Kokita in Medan. (2) partially the Marketing Strategy variables affected the Marketing Strategies of Kokita in Medan. (3) simultaneously there were positive and significant influences between variables Consumer Perception and Marketing Strategies influence Increased Sales of Kokita in Medan.